2019
DOI: 10.12962/j23546026.y2019i5.6344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Game Design and Playability Toward Continuance Intention Using TAM Framework

Abstract: As the growth of game industry, only few Studies in mobile games, and also focused on pre-adopting while ignoring post adoption behaviors. One intrinsic factor considered affecting gameplay is enjoyment. Some research has already conducted to understand what is enjoyment driver. Enjoyment is an external factor that influenced perceived usefulness. where perceived of usefulness is variable proposed in TAM. This study aims to examine impact the game design attribute that fit and influence enjoyment while play ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…According to several studies, PU is positively associated with continuance intention in the context of instant messaging (Wang, Ngai & Wei, 2012), mobile service provider (Abbas & Hamdy, 2015), online travel services (Li & Liu, 2014) e-learning (Lin & Wang, 2012) blog learning (Tang, Tang & Chiang, 2014), information establishment (Chou, Min, Chang & Lin, 2009). Moreover, previous studies indicated that there is a positive relationship between perceived usefulness and continuance intention (Suki et al, 2012;Pantouw & Aruan, 2019).…”
Section: The Effect Of Perceived Ease Of Use (Peou) On Continuance In...mentioning
confidence: 95%
“…According to several studies, PU is positively associated with continuance intention in the context of instant messaging (Wang, Ngai & Wei, 2012), mobile service provider (Abbas & Hamdy, 2015), online travel services (Li & Liu, 2014) e-learning (Lin & Wang, 2012) blog learning (Tang, Tang & Chiang, 2014), information establishment (Chou, Min, Chang & Lin, 2009). Moreover, previous studies indicated that there is a positive relationship between perceived usefulness and continuance intention (Suki et al, 2012;Pantouw & Aruan, 2019).…”
Section: The Effect Of Perceived Ease Of Use (Peou) On Continuance In...mentioning
confidence: 95%
“…El TAM se ha utilizado ampliamente para desarrollar herramientas de aplicación para evaluar y predecir si un sistema de información o una tecnología de la información será aceptada por los usuarios. La principal ventaja del TAM es que cuenta con un modelo de análisis cuantitativo sistemático y una rica experiencia acumulada en su uso para evaluar la aceptación de los videojuegos serios [44]. Se utilizaron los resultados de la validación del diseño para realizar una nueva iteración del diseño del videojuego, para a partir de esa nueva versión, iniciar con el desarrollo de un prototipo de alta fidelidad del videojuego, es decir, un prototipo funcional.…”
Section: Evaluarunclassified
“…Selera Nusantara Game has a Challenge that is not too heavy because it is designed to be played in a relaxed situation and does not require a lot of time, but still provides an attraction for its players. The Challenge here is a positive Challenge that provides happiness for its users [15]. Game Designer provides simple Challenges such as adding buyers with more orders at each level increase, but with a limited time.…”
Section: Widhiyanti Dewangga Almukthar (Game Design Factor Questioner...mentioning
confidence: 99%